The Systematic Evaluation of Instruments Designed to Assess Pain in Persons with Limited Ability to Communicate* - Michèle Aubin; Anik Giguère; Thomas Hadjistavropoulos; René Verreault (Pain Research and Management)
Chronic pain is often underdetected and undertreated in long-term care facilities. The use of self-report measures of pain (such as the visual analogue scale) is often problematic for older adults residing in long-term care because of the high prevalence of visual and auditory deficits and severe cognitive impairment. Observational measures of pain have been developed to address this concern. A systematic grid designed to assess the properties of existing observational measures of pain was used for seniors with dementia. The grid focused on the evaluation of content validity (12 items), construct validity (12 items), reliability (13 items) and clinical utility (10 items). Among the 24 instruments that were evaluated, several were deemed to be promising in the assessment of pain among older persons with severe dementia. Nonetheless, additional research is needed before their routine integration in the practices of long-term care settings.